ANALISIS STRUKTUR GEDUNG BERTINGKAT PASCA BENCANA ALAM DENGAN MENGGUNAKAN APLIKASI WORKSHEET - Marwahyudi . (Universitas Sahid Surakarta, 2010)
Building is a place of activity and interaction among it’s occupants. There fore, the protectian of the strength of building structure must be noticed well. Same dangers that likely to happen are flood, eartquake and corrosive. This research is aimed at knowing the strength of concrate residue. The method used in this research are visual observation, distructive and non destructive test. Distructive method uses hammer test,while non destructive uses compresssion test machine. The result of hammer test is counted by normal and homogeneuos data test. Then, the result of distructive and non destructive test are declaredto be received if the width more than 80% the strength of concrate residue (250kg/cm 2). It can be concluded that the result of destructive, non destructive and analysis are the demage of building 10.1 %, wall 8.5 %, column 1.4 % (there are two column damage), bean 0.3 % (one beam demage). Several damagae building structure are strengthened by carbon fibre stripe.